PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA BANK KALSEL SYARIAH AMUNTAI TENGAH KABUPETAN HULU SUNGAI UTARA - Hasanah, Nurul (Inovatif Jurnal Administrasi Niaga, 2019)
This study aims to determine the effect of service quality on customer satisfaction at the Central Kalimantan Shunt Bank Amuntai Tengah Hulu Sungai Utara. The method used in this study uses quantitative research methods. The results of the study prove that there is a positive and significant effect between service quality on customer satisfaction at the Sharia Bank of the Amuntai Branch Office. If the quality of service increases, customer satisfaction will also increase, conversely if the quality of existing services at the Sharia Bank of the Amuntai Branch Office decreases, customer satisfaction can also decrease.